Anterior Cruciate Ligament Preservation: Early Results of a Novel Arthroscopic Technique for Suture Anchor Primary Anterior Cruciate Ligament Repair - DiFelice, Gregory S; Villegas, Christine; Taylor, Samuel (Arthroscopy, 2015)
To propose a technique of arthroscopic suture anchor primary anterior cruciate ligament (ACL) preservation for patients with proximal avulsion ACL tears that maintain excellent tissue quality. We performed a retrospective review and early follow-up of 11 consecutive cases of ACL preservation. Patients were included if they had a proximal avulsion tear and excellent tissue quality confirmed to be adequate for repair during arthroscopy. Patients were excluded if these criteria were not met or if patients had multiligamentous injury patterns or significant arthrosis. The ACL was reinforced with a No. 2 FiberWire (Arthrex, Naples, FL) and a No. 2 TigerWire (Arthrex) and was anchored to the femoral footprint by two 4.75-mm BioComposite SwiveLock suture anchors (Arthrex). The surgical procedures were performed at 3 different hospitals by a single surgeon. Anterior stability was determined with a KT-1000 arthrometer (MEDmetric, San Diego, CA). Clinical outcomes were measured using the Lysholm score, modified Cincinnati score, Tegner activity score, Single Assessment Numeric Evaluation, and subjective and objective International Knee Documentation Committee (IKDC) scores. Ten of eleven patients had good subjective and clinical outcomes after ACL preservation surgery at a minimum of 2 years' and mean of 3.5 years' follow-up. The mean Lysholm score was 93.2; the mean modified Cincinnati score was 91.5; the preoperative Tegner activity score was maintained postoperatively in 8 of 10 patients; the mean Single Assessment Numeric Evaluation score was 91.5; the mean subjective IKDC score was 86.4; and the objective IKDC score was A in 9 of 11 patients, B in 1 patient, and C in 1 patient. KT-1000 measurements were available in 8 of 11 patients, with 7 of 8 showing a side-to-side difference of less than 3 mm on maximum manual testing and 1 showing a 6-mm difference. Preservation of the native ACL using the described arthroscopic primary repair technique can achieve short-term clinical success in a carefully selected subset of patients with proximal avulsion-type tears and excellent tissue quality. Level IV, therapeutic case series.